Lighting Rural India : Experience of Rural Load Segregation Schemes in States - World Bank (Washington, DC, 2014)
This paper summarizes the findings of a study in rural load segregation for lighting rural India. The study focused on (i) analyzing differences in approach to rural feeder segregation across states, (ii) assessing the financial viability of the schemes, (iii) evaluating socio economic benefits in rural areas through primary survey, and (iv) developing a guidance note for a national action plan on rural load segregation. Traditionally, power supply to agriculture in India has been heavily subsidized since irrigated agriculture was at the heart of the Green Revolution. The magnitude of the power subsidy for the agricultural sector in some states is twice the budgetary annual spending on health or rural development. It is in this context that several states in India have undertaken programs of rural feeder segregation which involve separation of rural non-agricultural and agricultural consumers by connecting them to separate feeders, thereby physically separating paid and nominally-paid loads. The two key findings of the study are (i) a one size fits all approach will not work across states given wide variety in local context and challenges, and (ii) all feeder segregation proposals should be evaluated as part of a larger strategic rural power supply improvement program.